Juvenile Idiopathic Arthritis in a New Rheumatology Clinic in Nigeria - Babatunde Hakeem OLAOSEBIKAN; Richard Oluyinka AKINTAYO; Barakat Adeola ANIMASHAUN; Olufemi Oladipo ADELOWO (Journal of Advanced Rheumatology Science, 2017)
Objectives: To describe the frequency, clinico-laboratory characteristics and treatment outcomes of patients with juvenile idiopathic arthritis (JIA) in Lagos State University Teaching Hospital (LASUTH), Lagos, Nigeria. Methods: This is a retrospective review of patients with JIA seen over a five-year period at the rheumatology clinic and children ward of LASUTH. We reviewed the folders of 28 patients from our unit records. The demographics, baseline clinical and laboratory characteristics, treatment given and patient outcomes were extracted and analyzed. Results: A total of 28 patients with JIA were managed over the study period. Twenty one (75%) patients among our JIA cases were female and the mean age at presentation was 9.8±3.9 years. The mean duration of symptoms before diagnosis was 21.8±5.7 months. Polyarticular JIA (PJIA) constituted 14 (50%) cases, while oligoarticular and systemic-onset JIA (SoJIA) constituted 9 (39.3%) and 5 (17.9%) of the JIA cases respectively. Anaemia was present in 20 (71.4%) patients, leucocytosis in 16 (57.1%) and thrombocytosis in 11 (39.2%). Twenty five (89.2%) patients had elevated erythrocyte sedimentation rates (ESRs), 21 (75%) had elevated C-reactive protein levels and 23 (82.1%) patients had hyperferritinaemia. Positive antinuclear antibody (ANA) was found in 5 (17.8%) patients. Mortality was documented in 2 (7.1%) patients both of whom were SoJIA cases. Eleven (39.3%) patients were lost to follow up. Conclusion: Unlike the common report of oligoarticular JIA (OJIA) being the most frequent subtype of JIA in various series from North America and Europe, PJIA was the most frequent subtype seen among our patients and this variant accounted for half of all JIA cases seen. There were no cases of psoriatic, enthesitis-related or undifferentiated JIA and most patients had haematological abnormalities and high levels of inflammatory markers at presentation.
Keywords: Arthritis